Analýza akrylamidu metodou GC-MS - Papoušek, Roman; Nováková, Petra; Marková, Eva; Barták, Petr (Chemické listy, 2013)
The study deals with the GC-MS determination of acrylamide in various matrices. The proposed method involves bromination of acrylamide to 2,3-dibromopropanamide, its conversion to 2-bromopropenamide and the GC-MS determination. The method was used for the determination of acrylamide in water, gaseous products of combustion and in food such as potato chips and cookies. The measured concentrations of acrylamide ranged from 46 to 1980 g kg–1 the highest levels being found in ground coffee and tobacco smoke.
Keywords: akrylamid; halogenace; Gas Chromatography-Mass Spectrometry; Food Safety; Acrylamide; Chromatography, Gas; Maillard Reaction; chromatografie plynová; bezpečnost potravin; plynová chromatografie s hmotnostně spektrometrickou detekcí; hmotnostní spektrometrie; Maillardova reakce; pitná voda; Mass Spectrometry; Drinking Water; Halogenation